Employee Performance Appraisal Model for State Civil Apparatus Based on The 360-Degree Feedback Method at The Civil Service Agency and Human Resources Development of Sukabumi City - Listiani, Teni; Liswara , Cyntha Dwi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the employee performance appraisal system for State Civil Apparatus (ASN) at the Civil Service and Human Resources Development Agency (BKPSDM) of Sukabumi City and proposes a 360-degree feedback–based model. Existing appraisals remain supervisor-centered, producing uniformly “good” ratings that reflect weak objectivity, limited participation, and minimal developmental use. Using a qualitative case study with structured interviews and document analysis, the findings identify subjectivity, inconsistent indicators, hierarchical constraints, and limited coaching. The proposed model integrates supervisors (40%), peers (25%), subordinates (20%), and self-assessment (15%), aligns with BerAKHLAK values, and emphasizes transparency, validation, feedback, and continuous improvement.